The effects of a prolonged running exercise on strength characteristics - Lepers, R.; Pousson, M. L.; Maffiuletti, N. A.; Martin, A.; Van Hoecke, J. (International Journal of Sports Medicine, 2000)
The aim of this study was to examine concentric, isometric, and eccentric strength reductions in the quadriceps muscle following a prolonged running exercise. Before and after a 2 h run (28.4+/-1.4 km) peak torque (PT) of the knee extensors at angular velocities of -120, -90, -60, 0, 60, 120, 180, 240 degrees x s(-1) using an isokinetic dynamometer, electromyographic (EMG) activity of the vastus lateralis (VL) and vastus medialis (VM) muscles and height of a counter movement jump were recorded in twelve well-trained triathletes. Counter movement jump performances decreased by 10% and PTvalues were all significantly lower (p < 0.01) at each angular velocity following the run. The torque loss was significantly (p < 0.01) greater under eccentric contractions (from 18 to 21%) than under concentric ones (from 11 to 14%). EMG activity (RMS) was lower in both VL and VM muscles after the 2 h run but no difference existed in RMS losses between concentric and eccentric contractions. The present results demonstrate that 1) a prolonged running exercise more greatly affects eccentric force production in the quadriceps muscle, and 2) this specificity seems to be due to an impairment of the muscular contractile mechanism rather than a modification to the neural input.